Diagnostic Accuracy of Methylated SEPT9 for Blood‐based Colorectal Cancer Detection: A Systematic Review and Meta‐Analysis. Issue 1 (January 2017) - Nian, Jiayun; Sun, Xu; Ming, SuYang; Yan, Chen; Ma, Yunfei; Feng, Ying; Yang, Lin; Yu, Mingwei; Zhang, Ganlin; Wang, Xiaomin
Abstract : OBJECTIVES: : More convenient and effective blood‐based methods are believed to increase colorectal cancer (CRC) detection adoption. The effectiveness of methylated SPET9 for CRC detection has been reviewed in the newly published recommendation statement by US Preventive Services Task Force (USPSTF), while detailed instructions were not provided, which may be a result of insufficient evidence. Therefore, more evidence is needed to assist practitioners to thoroughly understand the utilization of this special maker. METHODS: : Based on the standard method, a systematic review and meta‐analysis was performed. Quadas‐2 was used to assess the methodological quality of studies. Relevant studies were searched and screened from PubMed, Embase and other literature databases up to June 1, 2016. Pooled sensitivity, specificity and diagnostic odds ratio were summarized by bivariate mixed effect model and area under the curve (AUC) was estimated by hierarchical summary receiver operator characteristic curve. RESULTS: : 25 studies were included for analysis. The pooled sensitivity, specificity and AUC were 0.71, 0.92 and 0.88, respectively. Among the various methods and assays, Epipro Colon 2.0 with 2/3 algorithm was the most effective in colorectal cancer detection. Positive ratio of mSEPT9 was higher in advanced CRC (45% in I, 70% in II, 76% in III, 79% in IV) and lower differentiation (31% in high, 73% in moderate, 90% in low) tissue. However, this marker has poor ability of identifying precancerous lesions according to current evidence. CONCLUSIONS: : mSEPT9 is a reliable blood‐based marker in CRC detection, particularly advanced CRC. Epipro Colon 2.0 with 2/3 algorithm is currently the optimal method and assay to detect CRC.